REAL EARNINGS MANAGEMENT AND PROFITABILITY ON COMPANIES LISTED ON JAKARTA ISLAMIC INDEX - Gazali, Ahmad; oktaviana, Ulfi kartika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Objective of this research is to find the influence of Real Earnings Management (Operating cash flow, production costs, and cost Discretionary) towards the profitability of ROA in the companies listed on the Jakarta Islamic Index of period 2012-2017. The sampling method using purposive and analysis of research data using multiple regression analysis. Operating cash flow (CFO) gives a positive and significant effect on performance of the company (ROA). The production costs (PROD) and the cost of Discretionary (DISEXP) are not significant but giving positive effects on performance of the company. This shows that the Real Earnings Management in production costs and the cost of discretionary does not affect the company's Profitability at the company indexed in JII.